Perioperative or intraoperative blood transfusion increases the risk of postoperative pancreatic fistula following pancreaticoduodenectomy - Aktas, Aydin; Burak Cekic, Arif; Ates, Muhammet; Emre Reis, Murat; Ulusahin, Mehmet; Guner, Ali; Turkyilmaz, Serdar (Annals of Medical Research, 2021)
Aim: Postoperative pancreatic fistula (POPF) is one of the most common causes of morbidity following pancreaticoduodenectomy (PD). The optimum way of reducing the prevalence of POPF is to prevent its development. In this study, we attempted to identify the potential perioperative risk factors of POPF and suggestions were made for its. Material and Methods: In this study, we included patients who had undergone PD from January 2010 to April 2020. POPF was defined as per the International Study Group on Pancreatic Fistula. The patients were followed up for 30 days for POPF.Results: Fifty-two (52) patients whose medical records were available were enrolled. POPF developed in 19 patients (36.5%). Grade-A POPF developed in six patients (11.5%), Grade-B POPF in eight patients (15.4%), and Grade-C POPF in five patients (9.6%). Percutaneous drainage was performed in a patient with Grade-B POPF, and reoperation was performed for five patients with Grade-C POPF. In univariate analysis, female sex (p=0.03), perioperative blood transfusion (p=0.03), and the number of harvested lymph nodes ≥12 (p=0.008) were related to POPF. In logistic regression analysis, the number of harvested lymph nodes ≥12 (p=0.005) and female sex (p=0.03) were independent risk factors of POPF. Although perioperative blood transfusion increased the POPF risk, the effect was not statistically significant (p=0.10).Conclusion: POPF was observed to be the most important cause of morbidity following PD in our study. We also found that reduce the POPF risk, it is important to avoid blood transfusion whenever possible.
Keywords: Pancreatic fistula; whipple; risk factor; morbidity; outcome